The Historical Presidency: Lost Confidence: The Democratic Party, the Vietnam War, and the 1968 Election. Issue 3 (2nd February 2018) - Nelson, Michael
Abstract : The 1968 election was a crucial turning point for the Democratic Party. Long‐standing confidence by Democrats in the ability and responsibility of the United States to spread liberal values across the globe gave way to diffidence and hesitancy in the international arena in the face of growing disillusionment within the party about the Vietnam War. John F. Kennedy, with resolve, and Lyndon B. Johnson, with reservations, unsuccessfully pursued victory in the war, thereby creating the conditions for a revolt within their party that doomed Hubert H. Humphrey's candidacy in 1968 and led Democrats to turn against liberal assertiveness on the world stage for nearly the next quarter century.